Aplikasi Data Mining Untuk Menentukan Masa Studi Mahasiswa Menggunakan Metode Association Rule - alwendi, alwendi; Andi Saputra Mandopa (Jurnal Pendidikan Dewantara, 2023)
The development of data mining cannot be separated from technological developments, especially in determining association rules to determine the relationship between elements/attributes in the process of students receiving information at any point in time. When it comes to permissions, there are many factors that influence permissions. However, not all of these factors are considered important so research is carried out to determine the relationship between these factors. The topic research method is data collection and data analysis. By using the Association Rule technique we can obtain information from large data such as data from universities. The aim of this research is to determine the pattern of study duration for Graha Nusantara University F-KIP students. using the Association Rule Data Mining method and comparing a priori algorithms and hash-based algorithms. The data used is Graha Nusantara University F-KIP master data which is processed using the Association Rule Data Mining technique with an a priori algorithm and a hash-based algorithm with a minimum support of 1% and a minimum confidence of 1%. The results of data processing with the a priori algorithm are the same as the results of data processing with the hash-based algorithm, namely 49 2-itemset combinations.